PENGARUH KESESUAIAN NILAI ORGANISASIONAL DAN TUNTUTAN KEMAMPUAN TERHADAP KEPUASAN KERJA:NEED-SUPPLIESSEBAGAIPEMEDIASI (STUDI PEGAWAI BALAI PENDIDIKAN DAN PELATIHAN ILMU PELAYARAN MALAHAYATI-ACEH) - Putri Nahrisyah, Fairuzzabadi (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
ABSTRACTThis study aims to measure the influence of organizational values and demands-abilities pemediasi by job satisfaction needs-supplies (study of employee education and Training Science Hall Cruise Keumalahayati-Aceh). The sample used in this study are education and Science Hall employee Training Cruise Keumalahayati-Aceh totalling 150 respondents. Data collection tools used in this study was a detailed questionnaire. Sampling technique used is the Total sampling. Hierarchical Linear Modelling (HLM) is used as a method of analysis to find out the effects of all the variables involved. The results showed: 1) the suitability of the value of organizational influence on employee job satisfaction and Training Science Education Hall Cruise Keumalahayati – Aceh. 2) claims the ability to employee job satisfaction and Training Science Education Hall Cruise Keumalahayati – Aceh. 3) suitability of the Value effect on Organizational Needs-Supplies employee education and Training Science Hall Cruise Keumalahayati – Aceh. 4) demands the ability to Needs-Supplies employee education and Training Science Hall Cruise Keumalahayati – Aceh. 5) Needs-Supplies effect on job satisfaction. 6) Needs-mediated influence of Kesesuian Supplies organizational values against employee job satisfaction and Training Science Education Hall Cruise Keumalahayati – Aceh. 7) mediate the influence of Supplies Needs-Demands-ability towards job satisfaction. Keywords: Organizational Values Congruence, Demand-abilities, Needs-Supplies and job satisfaction.